Resolving whole‐plant economics from leaf, stem and root traits of 1467 Amazonian tree species. Issue 7 (12th May 2021) - Vleminckx, Jason; Fortunel, Claire; Valverde‐Barrantes, Oscar; Timothy Paine, C. E.; Engel, Julien; Petronelli, Pascal; Dourdain, Aurélie K.; Guevara, Juan; Béroujon, Solène; Baraloto, Christopher
Abstract : It remains unclear how evolutionary and ecological processes have shaped the wide variety of plant life strategies, especially in highly diverse ecosystems like tropical forests. Some evidence suggests that species have diversified across a gradient of ecological strategies, with different plant tissues converging to optimize resource use across environmental gradients. Alternative hypotheses propose that species have diversified following independent selection on different tissues, resulting in a decoupling of trait syndromes across organs. To shed light on the subject, we assembled an unprecedented dataset combining 19 leaf, stem and root traits for 1467 tropical tree species inventoried across 71 0.1‐ha plots spanning broad environmental gradients in French Guiana. Nearly 50% of the overall functional heterogeneity was expressed along four orthogonal dimensions, after accounting for phylogenetic dependences among species. The first dimension related to fine root functioning, while the second and third dimensions depicted two decoupled leaf economics spectra, and the fourth dimension encompassed a wood economics spectrum. Traits involved in orthogonal functional strategies, five leaf traits in particular but also trunk bark thickness, were consistently associated with a same gradient of soil texture and nutrient availability. Root traits did not show any significant association with edaphic variation, possibly because of the prevailing influence of other factors (mycorrhizal symbiosis, phylogenetic constraints). Our study emphasises the existence of multiple functional dimensions that allow tropical tree species to optimize their performance in a given environment, bringing new insights into the debate around the presence of a whole plant economic spectrum in tropical forest tree communities. It also emphasizes the key role that soil heterogeneity plays in shaping tree species assembly. The extent to which different organs are decoupled and respond to environmental gradients may also help to improve our predictions of species distribution changes in responses to habitat modification and environmental changes.